Journeys to Resilience - Alexander-Kenneth Nagel; Lucie Gott (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer)
The article examines the phenomenon of “prepping” from the perspective of conversion research. Based on a qualitative content analysis of postings from a big prepper online forum in the U.S., it explores the causes and modalities of adopting prepping as a lifestyle. The causes include biographical instances, experiences of disaster and emergency, reports from others and a general sense of threat. As to the modalities, the transition into prepping appears to take place gradually, although disruptive incidents may serve as important triggers for the decision to become a prepper. By interpreting the adoption of prepping as a form of secular conversion, the article aims to contribute to recent discussions on religious-secular competition and provides a test case of how religious studies may contribute to the analysis of non-religious worldviews and lifestyles.